2002
DOI: 10.1080/106689202760181797
|View full text |Cite
|
Sign up to set email alerts
|

From Persuasion to Accommodation in Public Two-Year College Development

Abstract: This was the ürst of a series of papers presented February 20, 2001 at a national conference sponsored by North Texas State University held in the Omni Hotel Dallas, TX. The author relates the 1950 status of two-year college development, numbers and locations of university professors specializing in the üeld, and the need to persuade citizens they should have a public two-year college in their midst. Events are traced which led up to the overwhelming demand by the public in the late 1960s and early 1970s to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Young's 1950 doctoral dissertation, An Analysis and Evaluation of General Legislation Pertaining to Public Junior Colleges, is seminal to understanding his later efforts to start junior colleges. Endorsed by the Research Committee of the American Association of Junior Colleges (AAJC; Young, 2002), it begins with a review of demographic, economic, social, technological, and political data from the U.S. Bureau of the Census, the federal National Economic Bureau, and other sources. From this analysis, which foreshadowed his citizen's participation studies, Young concluded that prospects for the future development of junior colleges were bright.…”
Section: Young's Dissertation and Its Influencementioning
confidence: 99%
See 4 more Smart Citations
“…Young's 1950 doctoral dissertation, An Analysis and Evaluation of General Legislation Pertaining to Public Junior Colleges, is seminal to understanding his later efforts to start junior colleges. Endorsed by the Research Committee of the American Association of Junior Colleges (AAJC; Young, 2002), it begins with a review of demographic, economic, social, technological, and political data from the U.S. Bureau of the Census, the federal National Economic Bureau, and other sources. From this analysis, which foreshadowed his citizen's participation studies, Young concluded that prospects for the future development of junior colleges were bright.…”
Section: Young's Dissertation and Its Influencementioning
confidence: 99%
“…Additionally, the junior colleges had provided the secondary districts with a supplemental revenue stream that generated profits far beyond the costs associated with operation of the two-year programs. (Krebs et al, 1999, p. 25) Young also recommended sound planning in the establishment of separate junior colleges, a theme emphasized by leading experts at the time, including L. V. Koos, S. V. Martorana, and James Wattenbarger (Young, 2002). Writing in 1996, Young recalled that up until the mid-1950s, 2-year college establishment had been erratic, haphazard, and largely without plan.…”
Section: Community College Establishment In Illinoismentioning
confidence: 99%
See 3 more Smart Citations